2021
DOI: 10.1140/epjp/s13360-021-01489-7
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal behavior in a predator–prey model with herd behavior and cross-diffusion and fear effect

Abstract: In this manuscript, we investigate the fear effect on the spatiotemporal behavior of the predator-prey model with prey social behavior and cross-diffusive. Our main interest is to determine the existence of Turing patterns and the fear effect performed by predators on the prey population and the group defense. The fear can lead to a partition of the prey herd which is known as prey escaping. It is obtained that the system has rich dynamics elaborated by the presence of Turing patterns and Turing-Hopf bifurcati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…In the past few years, mathematical models have become increasingly popular in studying how predation fear affects the growth rate of prey [14][15][16][17][18][19][20]. Křivan [21] investigated the trade-off between foraging and predation using the Lotka-Volterra model, which considers the adaptability of both the prey and predator to maximize their fitness.…”
Section: Introductionmentioning
confidence: 99%
“…In the past few years, mathematical models have become increasingly popular in studying how predation fear affects the growth rate of prey [14][15][16][17][18][19][20]. Křivan [21] investigated the trade-off between foraging and predation using the Lotka-Volterra model, which considers the adaptability of both the prey and predator to maximize their fitness.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 In the real world, the spatial distribution of population is inhomogeneous, so it is particularly important to consider the reaction-diffusion predator-prey model. [16][17][18][19] Spatial patterns and spatially inhomogeneous periodic solutions are important research contents, but the stable periodic solutions in numerical simulation are often spatially inhomogeneous. Based on the model (1.1), Yang et al considered the spatial diffusion and the competition in predator and showed the Hopf bifurcation induced by time delay.…”
Section: Introductionmentioning
confidence: 99%
“…In the real world, the spatial distribution of population is inhomogeneous, so it is particularly important to consider the reaction–diffusion predator–prey model 16–19 . Spatial patterns and spatially inhomogeneous periodic solutions are important research contents, but the stable periodic solutions in numerical simulation are often spatially inhomogeneous.…”
Section: Introductionmentioning
confidence: 99%
“…Wang and Zou [8] proposed a reaction-diffusion convective predator-prey model, which incorporated the fear effect into the local response term of the model. The authors of [9][10][11][12][13][14] studied the effect of the fear effect on the models from different aspects.…”
Section: Introductionmentioning
confidence: 99%